Effect of intermittent normobaric hypoxia on aerobic capacity and cognitive function in older people. Issue 11 (November 2016) - Schega, Lutz; Peter, Beate; Brigadski, Tanja; Leßmann, Volkmar; Isermann, Berend; Hamacher, Dennis; Törpel, Alexander
Abstract: Objectives: Physical exercise, especially aerobic training, improves physical performance and cognitive function of older people. Furthermore, it has been speculated that age-associated deteriorations in physical performance and cognitive function could be counteracted through exposures to passive intermittent normobaric hypoxia (IH). Thus, the present investigation aimed at investigating the effect of passive IH combined with subsequent aerobic training on hematological parameters and aerobic physical performance ( V ˙ O 2 max ) as well as peripheral levels of the neurotrophin brain-derived neurotrophic factor (BDNF) and cognitive function. Design: Randomized controlled trial in a repeated measure design. Methods: 34 older participants were randomly assigned to an intervention group (IG) or control group (CG). While IG was supplied with passive IH for 90 min, CG breathed ambient air. Subsequently, both groups underwent 30 min of aerobic training three times per week for four consecutive weeks. Aerobic physical performance and cognitive function was tested with spiroergometry and the Stroop test. Blood samples were taken to measure hematological parameters and the peripheral serum BDNF-level. Results: We found increases in the values of hematological parameters, the time to exhaustion in the load test and an augmented and sustainable improvement in cognitive function within the IG of the older people only. However, in both groups, the V ˙ O 2 max and serum BDNF-level did not increase. Conclusions: Based on these results, hypoxic training seems to be beneficial to enhance hematological parameters, physical performance and cognitive function in older people. The current hypoxic-dose was not able to enhance the serum BDNF-level or V ˙ O 2 max .